A hunted population in recovery: Effective population size for South American sea lions from Patagonia - Grandi, Maria Florencia (2012)
Effective population size (Ne) is a parameter of central importance in evolutionary biology and conservation. Factors such as unequal sex ratios of breeding individuals, periodic fluctuation in population size and variance in reproductive success can affect the Ne in general. At present, South American sea lions, Otaria flavescens, from northern Patagonia, Argentina, belongs to one of the several populations that are recovering from overhunting which occurred in the early 20th century. Here, we present the estimate of Ne for this population that takes into account the effects of their polygynous mating system and variation in population size through time. The resultant overall Nes were 4171 ± 2450 or 4745 ± 2681 breeding animals depending on the inclusion of peripheral adult males. The estimated Nes are not critical, because they are close to the average mean minimum viable population for vertebrates (5000 breeding adults). Even though the northern Patagonian population of O. flavescens is increasing its abundance is still far below its historical numbers. The Ne estimated should be considered the minimum range to be maintained, especially in light of bycatch related to fishery interactions along the Patagonian coast. We emphasise the importance of estimating Ne for future management plans of the species within different populations. © 2012 Koninklijke Brill NV, Leiden.